2008
DOI: 10.2174/156652408785160907
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-10 in the Resolution of Airway Inflammation

Abstract: IL-10 can be considered an important agent in the resolution of inflammation. Originally named "cytokine synthesis inhibitory factor" for its ability to inhibit IFN-gamma and IL-2 production in Th2 cells, it is secreted by monocytes, macrophages, mast cells, T and B lymphocytes, and dendritic cells (DCs). IL-10 production and release by monocytic cells in response to allergic challenge is upregulated by TNF-alpha, and by negative feedback regulation of itself. However, it is also secreted by T regulatory cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
84
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 106 publications
8
84
0
4
Order By: Relevance
“…Moreover, in our study the levels of the antiinflammatory IL-10 were significantly increased in the OVA-CdM lungs, suggesting that BMC CdM attenuates allergic T H 2 inflammation through an IL-10-dependent mechanism. IL-10 has been shown to contribute to the reduction of airway inflammation (40). BMC CdM itself acted as an exogenous source of IL-10; however, we did not find a significant difference between the levels of IL-10 in the lungs of BMC CdM-treated control animals and untreated controls, suggesting that endogenous production of IL-10 in the allergic inflammatory environment may be an important component of elevated IL-10 levels found only in OVA-CdM lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in our study the levels of the antiinflammatory IL-10 were significantly increased in the OVA-CdM lungs, suggesting that BMC CdM attenuates allergic T H 2 inflammation through an IL-10-dependent mechanism. IL-10 has been shown to contribute to the reduction of airway inflammation (40). BMC CdM itself acted as an exogenous source of IL-10; however, we did not find a significant difference between the levels of IL-10 in the lungs of BMC CdM-treated control animals and untreated controls, suggesting that endogenous production of IL-10 in the allergic inflammatory environment may be an important component of elevated IL-10 levels found only in OVA-CdM lungs.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that administration of BMC CdM would induce the Tr1 through IL-10 found in the CdM with a similar, simultaneous up-regulation of IL-10 production by lung macrophages through APN. This would lead to a sustained production of endogenous IL-10 that may contribute to attenuation of inflammatory events (40).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in IL-10 following IN CpG were also TLR9 dependent. The inhibitory effects of IL-10 on allergic inflammation are well known and include regulation of eosinophilia [8], inhibition of the proliferation of various structural cell types [41], and regulation of airway inflammation through its inhibitory action on nitric oxide, a potent mediator of AHR [42,43]. Recent studies have shown that the adoptive transfer of IL-10-overexpressing DCs into OVA-sensitized and challenged mice ameliorates allergic asthma symptoms [44].…”
Section: Discussionmentioning
confidence: 99%
“…During asthma, IL-10 can inhibit eosinophilia via suppression of IL-5 and GM-CSF, regulate eosinophil apoptosis, and down-regulate IL-1. In addition, IL-10 can suppress nitric oxide production, an important component of airway inflammation [99]. Upregulation of IL-10 was also demonstrated to normalize blood pressure and endothelial function [100,101].…”
Section: Prioritization Of Candidate Genesmentioning
confidence: 97%